21-day tummy diet cookbook : 150 all-new recipes that shrink, soothe and satisfy - Vaccariello, Liz (The Readers Digest Association, Inc., 2014)
"150 all-new quick and easy recipes to help you extend and maintain the 21-Day Tummy Diet. Featuring sample menus for each phase, easy to follow tips on how to create your own Belly Buddy recipes, and inspirational stories from the Tummy Testers, who collectively lost 90 pounds in 3 weeks, shed 29 inches from their waists, and reported fewer digestive symptoms and happier tummies. Belly bulges plague millions of Americans. So does bloating, heartburn, and other tummy troubles. It's no coincidence. As Reader's Digest editor-in-chief and weight loss expert Liz Vaccariello revealed in 21-Day Tummy Diet, the same foods can both pack on the pounds and lead to gastrointestinal problems--and the culprits may surprise you. Luckily, there are also foods that can help us both shrink and soothe our stomachs. In 21-Day Tummy Diet Cookbook, you'll find 150 all-new quick and easy recipes featuring amazing Belly Buddies such as blueberries, potatoes, and tomatoes, including: &#8226 Fast and filling breakfasts such as Potato, Ham and Cheddar Hash and Blueberry Corn Muffins, plus all new variations on the Belly Soother Smoothie [bullet] Soothing and satisfying soups such as Italian Tomato and Meatball Soup and Chicken Chard Soup with Pasta [bullet] Nourishing entrees and one-dish mains such as Tex-Mex Cheeseburger, Hazelnut-Stuffed Pork Chops, and Chicken Mac and Cheese [bullet] Simply delicious sides and salads such as Cherry Tomato and Forbidden Rice Salad, Tuscan Green Beans, and Home-Fries [bullet] Delectable desserts such as Chocolate-Chip Walnut Cookies, Blueberry Shortcakes, and Mochachino Cupcakes Plus you'll find sample menus for each phase of the 21-Day Tummy Diet, easy-to-follow tips on how to create your own Belly Buddy recipes, and inspirational stories from the Tummy Testers, who collectively lost 90 pounds in 3 weeks, shed 29 inches from their waists, and all reported fewer digestive symptoms and happier tummies"--